Diversities in the Indian diaspora: nature, implications, responses - Jayaram, N. (ed.) (Oxford, 2011)
This collection explores the nature and manifestation of institutional and socio-cultural diversities among the large Indian diaspora. In doing so, it provides a comparative framework for understanding 'India out of India'. It studies Indian communities formed during the colonial era, the so-called 'old diaspora' (in Malaysia, Mauritius, and Trinidad), and those formed largely after India's independence, the so-called 'new diaspora' (in Canada, Israel, and the USA). The book highlights the civilizational moorings of Indian communities abroad, including the dynamics of religion, caste, gender, and identity construction at the individual level. The volume analyses in depth the processes of assimilation, integration, and the formation of multiple identities among diasporic communities, including the rediscovery of regional and linguistic diversities. The essays also examine the asymmetrical orientations between India and her diaspora, and discuss the locale State's policies and their effects on the diasporic communities.
Keywords: Diaspora-India